Pendampingan Pembuatan Prosedur Pemantauan Dan Tindakan Korektif (Ventilasi, Tata Letak Ruang, Dan Pengaturan AC) Di RSIA X Probolinggo - Serlly Frida Drastyana; Emilya Indahyati; Iqbalul Asror; Wahyu Fajar Ananta (STIKES Yayasan RS.Dr.Soetomo, 2026)
Under the Hospital Occupational Safety and Health Standards (K3RS), hospitals are required to conduct regular workplace environmental monitoring and implement corrective actions. The objective of this activity is to enhance RSIA X Probolinggoâ€™s capacity to develop and implement standard operating procedures (SOPs) for monitoring and corrective actions related to ventilation, room layout, and air conditioning settings as part of efforts to improve indoor air quality. The methods used include training, technical assistance, and assessments from October 2025 to January 2026.Â The target audience for this activity includes department heads, facility maintenance staff, and the hospital quality team. The outcome of the activity is the development of draft monitoring procedures and corrective action plans. The results of the activity indicate an increase in knowledge following the training and technical assistance.